2001
DOI: 10.1159/000045899
|View full text |Cite
|
Sign up to set email alerts
|

Lupus Nephritis in Children: Prognostic Significance of Clinicopathological Findings

Abstract: Background: We aimed to review our experience with childhood lupus nephritis (LN) in respect to the analysis of the clinical and histopathological presentation of LN and prognostic factors affecting the kidney and patient outcomes. Method: Forty-three children (39 girls, 4 boys) with biopsy-proven LN were included in the study. The mean age of the children was 12.0 ± 2.8 years. Based on the renal histopathology and clinical presentation, patients were treated with oral prednisone, intravenous pulses of methylp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
67
8
12

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(109 citation statements)
references
References 25 publications
22
67
8
12
Order By: Relevance
“…However, western studies reported a higher percentage of class III and IV LN than did our study. [20,29,30] The high proportion of patients with class V LN (35%) and low proportion of class III LN (5%) in our study in contrast to the 2-5% and 15-25% in other series respectively is not explainable. In the past, renal disease was the major cause of mortality in patients with JSLE, but with earlier diagnosis and newer methods of treatment, the outlook for patients with lupus nephritis has vastly improved.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…However, western studies reported a higher percentage of class III and IV LN than did our study. [20,29,30] The high proportion of patients with class V LN (35%) and low proportion of class III LN (5%) in our study in contrast to the 2-5% and 15-25% in other series respectively is not explainable. In the past, renal disease was the major cause of mortality in patients with JSLE, but with earlier diagnosis and newer methods of treatment, the outlook for patients with lupus nephritis has vastly improved.…”
Section: Discussioncontrasting
confidence: 56%
“…In 90% of SLE patients, LN appeared within two years of the onset of the disease. An earlier Turkish study of children with LN [29] reported class IV (64%) of LN as the most frequent histopathological pattern. Bakr [14] stated that the biopsy distribution of the pathological classes of LN in Egypt was as follows: class I 4.9%, class II 22%, class III 36.7%, and class IV 36.7%.…”
Section: Discussionmentioning
confidence: 90%
“…Although in the last decade, there has been a significant improvement in the morbidity and mortality of treated children with SLE, there remains a cohort of children who do not respond to conventional therapy with corticosteroids and cyclophosphamide and other immunosuppressive agents (28)(29)(30)(31)(32)(33). In addition, the side effects of cytotoxic immunotherapy (mainly relating to cyclophosphamide) are not inconsequential in children.…”
Section: Discussionmentioning
confidence: 99%
“…It is acknowledged that renal biopsy is not always possible, for instance due to the patient's critical clinical condition or due to lack of resources to safely perform the procedure. Nephrotic syndrome, hypertension and impaired renal function are all correlated with class III/IV LN (26)(27)(28). In cases when a renal biopsy cannot be performed, these symptoms should be considered as reflecting class III/IV LN and treated likewise.…”
Section: Recommendations For Lupus Nephritis -Treatment (Table 2 Figmentioning
confidence: 99%